Odkryć piękno w starości… . Kobieta w jesieni życia w świetle wybranych źródeł XIX i XX stulecia - Jankowska, Aldona (Starość i młodość w literaturze i kulturze, 2016)
The article will present the problems of women’s old age in the 19th and 20th centuries. The pictureof old age is ambivalent. On one hand old women are associated with wisdom and experience, but onthe other hand they are excluded from many fields of life. The old age is a difficult time for women anda kind of cultural taboo. This article is based on the books of Klementyna Hoffmanowa, FranciszekOlszewski and selected journalistic texts in women’s magazine “Bluszcz”.